Delineation of seven species of genus Channa from upper Assam region, India using sagittal otolith morphology - Jyotirmoy Sonowal; Moirangthem Kameshwor Singh; Shyama Prasad Biswas (Journal of Fisheries, 2020)
Morphology of sagittal otoliths of seven species of genus Channa from upper Assam, India was studied to obtain baseline information for their prospective role in taxonomic studies. In the present study, variations were recorded in morphological characteristics of sagittal otolith among the studied species. Of all the studied parameters, otolith shape, sulcus acusticus, ostium, and cauda, in particular, were found to be taxonomically important features for the identification of the species. The pentagonal shape of sagitta in Channa punctata, pseudo-ostiocaudal sulcus acusticus in C. marulius, bent concave ostium in C. stewartii, straight cauda in C. bleheri were found to be species-specific features. Sagitta size was smallest in C. gachua while the largest was recorded in C. striata. The proposed taxonomic keys enumerated through the combination of different otolith characters from the present investigation will be useful in the identification of these species when standard methodologies fail to deliver satisfactory results.